Acute high-intensity interval running increases markers of gastrointestinal damage and permeability but not gastrointestinal symptoms - Pugh, J. N.; Impey, S. G.; Doran, D. A.; Fleming, S. C.; Morton, J. P.; Close, G. L. (Applied Physiology, Nutrition, and Metabolism, 2017)
The purpose of this study was to investigate the effects of high-intensity interval running on markers of gastrointestinal (GI) damage and permeability alongside subjective symptoms of GI discomfort. Eleven male runners completed an acute bout of high-intensity interval training (HIIT) (eighteen 400-m runs at 120% maximal oxygen uptake) where markers of GI permeability, intestinal damage, and GI discomfort symptoms were assessed and compared with resting conditions. Compared with rest, HIIT significantly increased serum lactulose/rhamnose ratio (0.051 ± 0.016 vs. 0.031 ± 0.021, p = 0.0047; 95% confidence interval (CI) = 0.006 to 0.036) and sucrose concentrations (0.388 ± 0.217 vs. 0.137 ± 0.148 mg/L; p < 0.001; 95% CI = 0.152 to 0.350). In contrast, urinary lactulose/rhamnose (0.032 ± 0.005 vs. 0.030 ± 0.005; p = 0.3; 95% CI = -0.012 to 0.009) or sucrose concentrations (0.169% ± 0.168% vs. 0.123% ± 0.120%; p = 0.54; 95% CI = -0.199 to 0.108) did not differ between HIIT and resting conditions. Plasma intestinal-fatty acid binding protein (I-FABP) was significantly increased (p < 0.001) during and in the recovery period from HIIT whereas no changes were observed during rest. Mild symptoms of GI discomfort were reported immediately and at 24 h post-HIIT, although these symptoms did not correlate to GI permeability or I-FABP. In conclusion, acute HIIT increased GI permeability and intestinal I-FABP release, although these do not correlate with symptoms of GI discomfort. Furthermore, by using serum sampling, we provide data showing that it is possible to detect changes in intestinal permeability that is not observed using urinary sampling over a shorter time-period.